Children and young people's wellbeing post-disaster: Safety and stability are critical. (December 2015) - Gibbs, L.; Block, K.; Harms, L.; MacDougall, C.; Baker, E.; Ireton, G.; Forbes, D.; Richardson, J.; Waters, E.
Abstract: Children, young people and parents from communities affected by the February 2009 bushfires in Victoria, Australia, were interviewed four to five years post-fires as part of the Beyond Bushfires research study. Participant-guided mobile methods were used, in conjunction with interviews, with 35 people aged 4–66 years, to explore their current sense of place and community. Analysis of their stories revealed how children and young people sought safety and stability in the aftermath of a disaster experience in their home, school, social, recreational and work environments. For some families, this was a significant factor in a decision to move away from affected communities, whereas for others the familiarity of the local environment and community members counteracted the post-disaster disruption. The interplay of child, parent and grandparent mutual support and protection was evident, with friends, schools and communities also providing important support in creating safe environments for children.